2015
DOI: 10.7314/apjcp.2015.16.9.4109
|View full text |Cite
|
Sign up to set email alerts
|

Significance and Application of Digital Breast Tomosynthesis for the BI-RADS Classification of Breast Cancer

Abstract: Background: Full-field digital mammography (FFDM) with dense breasts has a high rate of missed diagnosis, and digital breast tomosynthesis (DBT) could reduce organization overlapping and provide more reliable images for BI-RADS classification. This study aims to explore application of COMBO (FFDM+DBT) for effect and significance of BI-RADS classification of breast cancer. Materials and Methods: In this study, we selected 832 patients who had been treated from May 2013 to November 2013. Classify FFDM and COMBO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…When comparing the ROC areas, it was found that DBT is significantly superior to DM in breast cancer diagnosis (AUC = 0.883 vs 0.619; p < 0.0001), and the BI-RADS with combined DM and DBT was significantly superior to BI-RADS with DM or BI-RADS with DBT alone (AUC: 0.971; p < 0.0001). Similarly, Cai et al [33] analyzed 79 cases with pathologic results by using ROC curve and showed that the AUC of the combined DM and DBT was greater than that of DM alone (0.914 vs. 0.805). Also, Thomassin et al [34] calculated AUC by averaging the ROC from four readers; the mean AUC for BI-RADS with combined DM and DBT was higher than that calculated for BI-RADS with DM alone (0.809 vs. 0.685; p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the ROC areas, it was found that DBT is significantly superior to DM in breast cancer diagnosis (AUC = 0.883 vs 0.619; p < 0.0001), and the BI-RADS with combined DM and DBT was significantly superior to BI-RADS with DM or BI-RADS with DBT alone (AUC: 0.971; p < 0.0001). Similarly, Cai et al [33] analyzed 79 cases with pathologic results by using ROC curve and showed that the AUC of the combined DM and DBT was greater than that of DM alone (0.914 vs. 0.805). Also, Thomassin et al [34] calculated AUC by averaging the ROC from four readers; the mean AUC for BI-RADS with combined DM and DBT was higher than that calculated for BI-RADS with DM alone (0.809 vs. 0.685; p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a lack of non-invasive methods for the molecular classification of breast cancer. On the basis of a previous study that indicated that the sensitivity of breast cancer diagnosis increases from 60% using traditional digital mammography to 82.9% using DBT (16), the present study investigated further the associations between breast cancer molecular subtypes and DBT imaging characteristics, including tumor margin, surrounding bright ring of tumor, vascular images and calcification foci, lymph node size and associations with surrounding glandular tissue. The aim of the present study was to demonstrate that DBT may serve as a clinical diagnostic tool for diagnosing molecular subtypes of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that DBT has important influence and significance in the classification of breast imaging-reporting and data system (BI-RADS). The diagnostic sensitivity increased from 60% with traditional digital mammography to 82.9% with DBT and the specificity of the two techniques used together was 93.2% (16). Primary indicators for BI-RADS classification include tumor margin, surrounding bright ring of tumor, vascular images and calcification foci, lymph node size, and associations with surrounding glandular tissue (1719), and identification of these indicators is improved in a tomographic image (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, radiologists can only recognize the calcifications with a diameter of >0.5 mm, and many micro-calcifications are missed. For instance, the occurrence rate of calcifications in screening X-rays is >40%, while the occurrence rate of calcifications in pathological sections is >70% (11,12). …”
Section: Discussionmentioning
confidence: 99%